Membrane Proteocomplexome of Campylobacter jejuni Using 2-D Blue Native/SDS-PAGE Combined to Bioinformatics Analysis - Guérin, Alizée; Sulaeman, Sheiam; Coquet, Laurent; Ménard, Armelle; Barloy-Hubler, Frédérique; Dé, Emmanuelle; Tresse, Odile (Frontiers in Microbiology, 2020)
Campylobacter is the leading cause of the human bacterial foodborne infections in the developed countries. The perception cues from biotic or abiotic environments by the bacteria are often related to bacterial surface and membrane proteins that mediate the cellular response for the adaptation of Campylobacter jejuni to the environment. These proteins function rarely as a unique entity, they are often organized in functional complexes. In C. jejuni, these complexes are not fully identified and some of them remain unknown. To identify putative functional multi-subunit entities at the membrane subproteome level of C. jejuni, a holistic non a priori method was addressed using two-dimensional blue native/Sodium dodecyl sulfate (SDS) polyacrylamide gel electrophoresis (PAGE) in strain C. jejuni 81–176. Couples of acrylamide gradient/migration-time, membrane detergent concentration and hand-made strips were optimized to obtain reproducible extraction and separation of intact membrane protein complexes (MPCs). The MPCs were subsequently denatured using SDS-PAGE and each spot from each MPCs was identified by mass spectrometry. Altogether, 21 MPCs could be detected including multi homo-oligomeric and multi hetero-oligomeric complexes distributed in both inner and outer membranes. The function, the conservation and the regulation of the MPCs across C. jejuni strains were inspected by functional and genomic comparison analyses. In this study, relatedness between subunits of two efflux pumps, CmeABC and MacABputC was observed. In addition, a consensus sequence CosR-binding box in promoter regions of MacABputC was present in C. jejuni but not in Campylobacter coli. The MPCs identified in C. jejuni 81–176 membrane are involved in protein folding, molecule trafficking, oxidative phosphorylation, membrane structuration, peptidoglycan biosynthesis, motility and chemotaxis, stress signaling, efflux pumps and virulence.